Impact of Fiscal Policies on Economic Growth and Income Distribution in the Digital Era - Bahri, Syamsul; Ahmad, Farhan; Agus, Muis (Journal Social Civilecial, 2024)
The paper also aims to examine how the characteristics of the digital age have affected the fiscal policies and economic growth and income distribution, and the political economy that underpins policymaking. With advancing technologies transforming the economy around the globe, conventional oriental ways of debtor nation treaties to solve fiscal measures’ weaknesses including the incapability to address increasing income disparity and sectoral imbalance. Thus, this work based on the qualitative research method involves the interviews of policymakers, economists, and stakeholders to identify their motives and concerns associated with fiscal outcomes. As this study establishes, digital economies may hold potential for economies to expand, these digital economies also perpetuate income disparity as shown where gig workers and sectors that are locked out of digital incentives are concerned. These shifts pose a risk to governments’ ability to fund critical expenses; however, the study calls for fiscals’ policies to embrace innovations with policies that promote fairness in resource distribution. In addition, it also highlights the position of political factors in the fiscal actions pointing that policies are made based on political beliefs and democracy interests of certain political positions. The research provides new insights to the existing literature through providing detailed knowledge of the relationship between fiscal policy, growth, and income distribution in the backdrop of digitalization. Accordingly, the need for local and revolutionary fiscal interventions that will fund the fair distribution of new-technology prosperity and promote responsible and inclusive new-economy growth are highlighted.